The making of modern economics : the lives and ideas of the great thinkers - Skousen, Mark (M.E. Sharpe, 2009)
"Provides an accessible introduction to the major economic thinkers of the past 225 years - including little-known and often amusing facts about their personal lives"--Publisher description